Playful multimodal activation with assessment of neuropsychological profiles in Alzheimer's disease: Developing topics. (7th December 2020) - Paletta, Lucas; Russegger, Silvia; Pszeida, Martin; Murg, Sandra; Orgel, Thomas; Dini, Amir; Jos, Anna; Schuster, Eva; Koster, Ernst HW; Steiner, Josef; Fellner, Maria
Abstract: Background: A key problem in developing interventions in dementia care is the lack of knowledge about the mental processes and individual dependencies between functional impairments evolving over time. Neuropsychological profiles reflect the impact of the disease on distinctive neuroanatomic networks associated with complex cognitive domains. Recently serious games have been successfully validated with high potential as dementia biomarkers but increased estimation accuracy and personalised neuropsychological profiling is still required. Method: Tablet‐PC‐based intervention was applied within 10 weeks in Austria, engaging persons with dementia (PwD) with Alzheimer's disease (AD) living at home in terms of playful multimodal training and activation (n=15, age M=81.7 years, MoCA score M=17.9). PwDs interacted with an integrated version of two serious games: (a) 15 PwD played 'MIRA', a playful version of the anti‐saccade task, and (b) 8 PwD played 'MMA', a suite of cognitive exercises (puzzle, memory, text gap filling). The games were introduced and assisted by trainers, some PwD learned to play alone. Result: The score of gaze‐based MIRA showed significant correlation with MoCA score (Rho= .713**) and enabled individual MoCA score estimates with errors of less than M=2.6 MoCA points. MMA showed correlation with MoCA (Rho=p=.755*) and further MoCA subscores so that the neuropsychological profile could be established including impairments in visuospatial operations, attention, abstraction, language and recall. Conclusion: The work outlined within the EU project PLAYTIME indicates successful steps towards daily use of gaze‐based games. MIRA together with the MMA training enables continuous estimates of Alzheimer's mental state in general but also to estimate individual neuropsychological profiles to identify personal impairments and their course over time. The playful training app was very well accepted by PwD users and offers with its pervasive mental assessment tool a large potential for future long‐term monitoring in numerous AD care services.